Bella [videorecording (DVD)] - Monteverde, Alejandro; Verástegui, Eduardo, 1974-; Blanchard, Tammy; Pérez, Manny (Lionsgate, 2008)
An international soccer star is on his way to sign a multimillion dollar contract when a series of events unfold that brings his career to an abrupt end. A beautiful waitress, struggling to make it in New York City, discovers something about herself that she's unprepared for. In one irreversible moment, their lives are turned upside down-- until a simple gesture of kindness brings them both together, turning an ordinary day into an unforgettable experience.